A fast and practical method for initial diagnosis of Piscinoodinium pillulare outbreaks: piscinootest - Silva Gomes, Ana Lucia; Costa, Jesaias Ismael da [UNESP]; Flora de Novaes Benetton, Maria Linda; Bernardino, Geraldo; Belem-Costa, Andrea (Univ Federal Santa Maria, 2018)
The dinoflagellate Piscinoodinium pillulare is a parasite with low parasitic specificity and unspecific geographical distribution. This research reported a simple and practical method - the principle of spontaneous sedimentation - to identify the presence of P. pillulare during massive infestations which does not require using precision equipment. Agitation in water of the gill arches of infested fish will elicit, after a period of rest, recording the accumulation of trophonts in the bottom of flasks. The method was applied during outbreaks of P. pillulare in tambaqui, Colossoma macropomum and matrinxa, Brycon amazonicus, in fish farms of the Amazon region and proved to be effective.
Keywords: fish parasite; dinoflagellate; piscinoodiniasis